IMF Survey : Volume 28, Issue 03. (IMF Survey; IMF Survey, 1999)
On January 22, the IMF announced that more than 85 percent of its members had consented to an increase in the IMF's quotas. The text of Press Release No. 99/4, issued on January 22, follows.